Study of B c + → χ c π + decays - Aaij, R; Abdelmotteleb, ASW; Abellan Beteta, C; Abudinén, F; Ackernley, T; Adefisoye, AA; Adeva, B; Adinolfi, M; Adlarson, P; Agapopoulou, C; Aidala, CA; Ajaltouni, Z; et al. (Springer, 2024)
A study of Bc+→χcπ+ decays is reported using proton-proton collision data, collected with the LHCb detector at centre-of-mass energies of 7, 8, and 13 TeV, corresponding to an integrated luminosity of 9 fb−1. The decay Bc+→χc2π+ is observed for the first time, with a significance exceeding seven standard deviations. The relative branching fraction with respect to the Bc+→J/ψπ+ decay is measured to beBBc+→χc2π+BBc+→J/ψπ+=0.37±0.06±0.02±0.01, where the first uncertainty is statistical, the second is systematic, and the third is due to the knowledge of the χc2→ J/ψγ branching fraction. No significant Bc+→χc1π+ signal is observed and an upper limit for the relative branching fraction for the Bc+→χc1π+ and Bc+→χc2π+ decays of BBc+→χc1π+BBc+→χc2π+=<0.49 is set at the 90% confidence level.